Analisa Unjuk Kerja Sucker Rod Pump C-228 D – 213 – 86-7466 Sebagai Metode Pengangkatan Buatan Produksi Minyak Bumi untuk API 15° dan 45° - Edward Hamid Muhammad; Hadziqul Abror; Eriska Eklezia Dwi Saputri; Riska Laksmita Sari; Welayaturromadhona Welayaturromadhona (Politeknik Negeri Padang, 2022)
The oil production process is the process of extracting oil from the reservoir using the wells that have been made. In the production process there are three stages, namely primary recovery, secondary recovery and tertiary recovery. At the primary recovery stage there are two methods, namely production using natural reservoir energy (natural flow) and production using artificial lift methods (artificial lift). There are two basic principles of artificial lift, namely gas lift and pumps. The principle of the gas lift is to inject gas into the bottom of the well thereby reducing the density and pressure gradient of the reservoir fluid so that the fluid flows more easily. While the principle of the pump is to provide additional energy (head) to lift the fluid. The type of pump that is often used for shallow wells is Sucker Rod Pump. The performance of the sucker rod pump is influenced by the characteristics of the well and reservoir such as pressure, well productivity, physical properties of the fluid, as well as the depth of the well and the dimensions of the sucker rod pump. In this study, the factors studied were the physical properties of the fluid, namely the API of the fluid with variations of API 15o and API 45o, as well as the pump volumetric efficiency (Ev) of 90% and 70%. From the analysis carried out, the results obtained a). For API 15° and Ev 90% fluids: 759 stb/day and 39 hp prime mover power; and for API 15° and Ev 70%: 591 stb/day and prime mover power of 32.2 hp. b). For API 45° and Ev 90% fluids: 783 stb/day and prime mover power of 34.3 hp; and for API 45° and Ev 70%: 609 stb/day and prime mover power of 28.6 hp.